2021
DOI: 10.1186/s12877-021-02261-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of COVID-19 in older adults: a systematic review and meta-analysis

Abstract: Background Few studies have focused on exploring the clinical characteristics and outcomes of COVID-19 in older patients. We conducted this systematic review and meta-analysis to have a better understanding of the clinical characteristics of older COVID-19 patients. Methods A systematic search of PubMed and Scopus was performed from December 2019 to May 3rd, 2020. Observational studies including older adults (age ≥ 60 years) with COVID-19 infection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
96
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 42 publications
(42 reference statements)
12
96
1
3
Order By: Relevance
“…This study showed that hypertension was the most common comorbidity in this study, and elderly patients frequently presented with DM, COPD, cardiovascular disease, and heart failure. These results are similar to those of other studies showing that patients commonly had hypertension, and diabetes, cardiovascular disease, hypercholesterolemia, chronic lung disease, and malignancy were the frequent comorbidities [20][21][22][23][24]. In this research, elderly patients had lower NLRs, hemoglobin and albumin levels, and higher BUN levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study showed that hypertension was the most common comorbidity in this study, and elderly patients frequently presented with DM, COPD, cardiovascular disease, and heart failure. These results are similar to those of other studies showing that patients commonly had hypertension, and diabetes, cardiovascular disease, hypercholesterolemia, chronic lung disease, and malignancy were the frequent comorbidities [20][21][22][23][24]. In this research, elderly patients had lower NLRs, hemoglobin and albumin levels, and higher BUN levels.…”
Section: Discussionsupporting
confidence: 91%
“…Tan et al showed that 47.2% of patients who died from COVID-19 were elderly (≥70 years) [19]. Singhal et al revealed that 51% of older patients with COVID-19 (≥60 years) had severe infection and 22% of patients were critically ill [20]. In the study by Agnieszka et al, 50% of elderly patients with COVID-19 (≥60 years) were hospitalized (50.5%), of whom 23.5% were admitted at the ICU [21].…”
Section: Discussionmentioning
confidence: 99%
“…There is consistent evidence that healthcare workers on the frontline, older adults, and particularly elderly people with comorbidities have been at higher risk and poorer outcome when infected by the new Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) [1,2]. Reduced effectiveness of the immune system associated with advanced age (immunosenescence) has shown to be a contributory factor in the development of severe COVID-19 [3].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical symptoms of COVID-19 range from asymptomatic to severe cardiopulmonary disease (16)(17)(18). Enhanced expression of ACE2 and immunosuppressive states caused by malignancies and anticancer treatments, such as chemotherapy or surgery, contribute to more severe disease in older patients with COVID-19 (19,20).…”
Section: Introductionmentioning
confidence: 99%